OXYGEN ISOTOPE VARIATIONS IN OCEAN ISLAND BASALT PHENOCRYSTS - Eiler J.M.; Farley K.A.; Stolper E.M.; Valley J.W.; Hauri E.; Craig H.; Hart S.R. (My University, 1997)
Oxygen isotope ratios are reported for olivine phenocrysts from sixty-seven samples of ocean island basalts (OlBs), mid-ocean ridge basalts (MORBs), and related peridotites, including representatives of the various isotopic endmembers defined by radiogenic isotope ratios. OIBs are more homogeneous in 6'8O by this analysis than suggested by previous studies of whole rocks and glasses. Most 0I13 samples have oxygen isotope ratios within a restricted range (δ18Oolivine = 5.0–5.4‰), comparable to those of olivines in peridotites from ophiolites, in most peridotitic mantle xenoliths, and inferred for the sources of mid-ocean ridge basalts. The exceptions are EM2 lavas, which are enriched in 18O (δ18olivine = 5.4–6.1‰), and a small number of samples characterized by low and distinctive lead isotope ratios, which are 18O depleted (δ18O = 4.7-5.1‰). The observed range in δ18O and the correlations with radiogenic isotope ratios are similar to those observed in a detailed study of Hawaiian samples (Eiler et al., 1996b). These results indicate that recycled crust and/or sediments (or the imprint of extensive metasomatism by fluids derived from such materials) is present as at most a small mass fraction (⪅ l%) in the mantle sources of most OIBs. The results on most EM2 lavas are consistent with the presence of ∼2–6% recycled sediment in their source regions. Low δ18O values in OIBs can be produced by assimilation of altered lavas from high-levels in the volcanic edifice, assimilation of the oceanic crust underlying the volcano, or incorporation of subducted oceanic crust in mantle sources. The only consistent correlatives with low δ18O are low and anomalous relationships, and most of the low-δ18O samples can be explained by contamination by the underlying oceanic crust or volcanic edifice. lavas are indistinguishable from MORBs and most other OIBs in terms of δ18O, suggesting that to the extent that the lower mantle is sampled by hotspot volcanism, there is no significant vertical stratification in oxygen isotope ratios in the mantle.